Reclassification of Agroecological Zones: Case Study at Nangapanda, Ende, East Nusa Tenggara - Paramitha Putri, Nadya; Frimawaty, Evi; Wibowo, Adi (Riviera Publishing, 2023)
An agroecological zone can be one of the agricultural planning assessments that consider the environment's physical conditions and the commodities suitable for those conditions. Mapping of agroecological zones in Indonesia has been carried out by the Ministry of Agriculture but on an extensive coverage (small scale) so that it is not representative at the district level. This study aims to update the spatial map of agroecological zones in Nangapanda District so the agroecological zones map becomes more detailed and more representative to be used as a reference for development at the district level, especially for agriculture. The assessment of agroecological zones will be based on the 2013 AEZ module of the Agricultural Research and Development Agency (BPPP) and carried out with spatial overlay analysis using a geographic information system. The results showed that on a scale of 1:50.000, the agroecological zones formed in Nangapanda were dominated by Zone IIay (dry lowland annual crops) with 9.120,87 ha (47,93%) followed by Zone I (forestry) with 8.432,29 ha (44,31%), Zone IIIay (dry lowland annual and food crops) 690,58 ha (3,63%), Zone IIby (dry midland annual crops) 517,69% (2,72%), and Zone IVay (dry lowland food crops) 270 ha (1,42%). These updated agroecological zones are very different from the 1:250.000 scale BPPP 2013 agroecological zones in terms of zoning, detail, dan spatial patterns. The results of this study are expected to help in planning and decision-making for planting commodities following the environment's physical conditions.